COVID-19 vaccination in patients with multiple sclerosis: What we have learnt by February 2021. (May 2021) - Achiron, Anat; Dolev, Mark; Menascu, Shay; Zohar, Daniela-Noa; Dreyer-Alster, Sapir; Miron, Shmuel; Shirbint, Emanuel; Magalashvili, David; Flechter, Shlomo; Givon, Uri; Guber, Diana; Stern, Yael; et al.
Background: Since vaccination against coronavirus disease 2019 (COVID-19) became available, risks related to vaccinating patients with multiple sclerosis (MS) need to be carefully assessed. Objective: Characterize safety and occurrence of immediate relapses following COVID-19 vaccination in a large cohort of MS patients. Methods: We assessed the safety of BNT162b2 COVID-19 vaccination in adult MS patients. Results: Between 20 December 2020 and 25 January 2021, 555 MS patients received the first dose of BNT162b2 vaccine and 435 received the second dose. There were three cases of COVID-19 infection encountered after the first dose. Safety profile of COVID-19 vaccine was characterized by pain at the injection site, fatigue, and headache. No increased risk of relapse activity was noted over a median follow-up of 20 and 38 days after first and second vaccine doses, respectively. The rate of patients with acute relapse was 2.1% and 1.6% following the first and second doses, respectively, similar to the rate in non-vaccinating patients during the corresponding period. Mild increase in the rate of adverse events was noted in younger patients (18–55 years), among patients with lower disability (Expanded Disability Status Scale (EDSS) ⩽3.0), and in patients treated with immunomodulatory drugs. Conclusion: COVID-19 BNT162b2 vaccine proved safe for MS patients. No increased risk of relapse activity was noted.